2017
DOI: 10.1039/c7cp03854b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the BrO + HO2 reaction over the temperature range T = 246–314 K

Abstract: The kinetics of the reaction between gas phase BrO and HO2 radicals, BrO + HO2 → HOBr + O2 (1), have been studied over the atmospherically relevant temperature range T = 246–314 K and at ambient pressure, p = 760 ± 20 Torr, using laser flash photolysis coupled with ultraviolet absorption spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…It is clearly important to establish the mechanism of the BrO + HO2 reaction and determine its rate coefficient at temperatures which are relevant to the troposphere (typically 220-320 K). Experimentally the rate coefficient of this reaction has been measured at different temperatures in this temperature range by a number of research groups (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and they show that the rate coefficient decreases as the temperature increases i.e. a negative temperature dependence is observed.…”
Section: Supplementary Information (A)atmospheric Importance and Summ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly important to establish the mechanism of the BrO + HO2 reaction and determine its rate coefficient at temperatures which are relevant to the troposphere (typically 220-320 K). Experimentally the rate coefficient of this reaction has been measured at different temperatures in this temperature range by a number of research groups (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and they show that the rate coefficient decreases as the temperature increases i.e. a negative temperature dependence is observed.…”
Section: Supplementary Information (A)atmospheric Importance and Summ...mentioning
confidence: 99%
“…They show computed schematic pathways in the work of Tsona et al(1) and Chow et al(2) respectively. The atmospheric importance of the BrO + HO2 reaction and the experimental rate coefficient (k) measurements, which show a negative temperature dependence of k, are summarized in the Suplementary Information (SI) section (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Our work, Chow et al (2), has shown that of the possible reaction channels i.e. ( 1) BrO + HO2 → HOBr + O2, (2) BrO + HO2 → HBr + O3 , (3) BrO + HO2 → OBrO + OH, (4) BrO + HO2 → BrOO + OH, (1) has the lowest activation energies and is the major contributor to the overall rate coefficient at temperatures relevant to the troposphere.…”
Section: Introductionmentioning
confidence: 99%